STRATEGIC ECONOMIC MECHANISMS FOR ENHANCING THE MANAGEMENT EFFICIENCY OF CONSTRUCTION ENTERPRISES - Yembergenova Aynur Aydosbayevna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
The construction sector is one of the key drivers of economic development, contributing significantly to infrastructure expansion, employment generation, and investment growth. In an increasingly competitive and dynamic business environment, construction enterprises face numerous challenges related to resource allocation, project implementation, financial sustainability, and technological transformation. These challenges require the application of effective economic mechanisms capable of improving management efficiency and organizational performance. This study examines strategic economic mechanisms that contribute to the effective management of construction enterprises. Particular attention is devoted to planning, decision-making, organizational coordination, risk management, motivation, and control as interconnected elements of a comprehensive management system. The paper also explores the role of digital transformation, innovative management tools, and modern governance approaches in enhancing enterprise competitiveness. The research demonstrates that the integration of economic mechanisms with strategic management practices improves resource utilization, strengthens operational performance, reduces managerial risks, and supports sustainable business growth. The findings may serve as a practical framework for managers, policymakers, and researchers interested in improving management systems within the construction industry.